2010
DOI: 10.1097/mao.0b013e3181e40e4f
|View full text |Cite
|
Sign up to set email alerts
|

B7-H1 Expression in Vestibular Schwannomas

Abstract: Hypothesis B7-H1 is expressed in vestibular schwannomas. Background Little is known about how benign human vestibular schwannomas interact with antibody-mediated or cell-mediated immunity. We report on the aberrant expression of a novel T-cell coregulatory molecule, B7 homolog 1 (B7-H1), in vestibular schwannomas and discuss the implications of B7-H1 expression and tumor aggressiveness and a potential regulator of B7-H1 expression. Methods Immunohistochemical staining for B7-H1, CD8+, CD3+, and CD4+ lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Furthermore, we found that the pre-treatment growth rates for tumors that continue to grow after radiosurgery are comparable to those that responded favorably to radiation and showed a decrease in growth. In other words there was no correlation between post-SRS continued growth and pre-treatment growth rate of VS. Tumors that continue growth after radiosurgery are most likely resistant to radiation because of varying intrinsic molecular properties [17] . It is important to acknowledge that in this study we examined the early changes in growth rates of VS following radiosurgery, and the results seen in early regression following treatment are not a unified concept and not necessarily directly correlated with long-term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the pre-treatment growth rates for tumors that continue to grow after radiosurgery are comparable to those that responded favorably to radiation and showed a decrease in growth. In other words there was no correlation between post-SRS continued growth and pre-treatment growth rate of VS. Tumors that continue growth after radiosurgery are most likely resistant to radiation because of varying intrinsic molecular properties [17] . It is important to acknowledge that in this study we examined the early changes in growth rates of VS following radiosurgery, and the results seen in early regression following treatment are not a unified concept and not necessarily directly correlated with long-term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…73 Given the evidence, supporting the upregulation of PD-L1 within VS that have not responded to primary treatment with SRS or surgery, there may be a rationale for immune checkpoint inhibition strategies targeted against the immunosuppressive activity of the PD-L1/PD-1 axis. 30,58 Recombinant anti-PD-1 antibodies have been used to dramatic effect in tumors with high levels of cytotoxic T-cell inhibition, such as melanoma. 74 There is also emerging evidence of the efficacy of such therapies in a subset of glioma patients, and they may represent a promising therapeutic avenue for patients with VS, particularly those with tumors that recur following surgery or SRS with high levels of PD-L1 expression.…”
Section: A Basis For New Therapies?mentioning
confidence: 99%
“…(1922) Several types of cancer have been analyzed for PD-L1 expression, but a comprehensive analyses, including rare germ cell and mesenchymal tumors has not been performed. (1013, 2325)…”
Section: Introductionmentioning
confidence: 99%